A Brain Penetrant Mutant IDH1 Inhibitor Provides In Vivo Survival Benefit. Issue 1 (December 2017) - Kopinja, Johnny; Sevilla, Raquel; Levitan, Diane; Dai, David; Vanko, Amy; Spooner, Edward; Ware, Chris; Forget, Robert; Hu, Kun; Kral, Astrid; Spacciapoli, Peter; Kennan, Richard; et al.
Abstract Mutations in IDH1 are highly prevalent in human glioma. First line treatment is radiotherapy, which many patients often forego to avoid treatment-associated morbidities. The high prevalence of IDH1 mutations in glioma highlights the need for brain-penetrant IDH1 mutant-selective inhibitors as an alternative therapeutic option. Here, we have explored the utility of such an inhibitor in IDH1 mutant patient-derived models to assess the potential therapeutic benefits associated with intracranial 2-HG inhibition. Treatment of mutant IDH1 cell line models led to a decrease in intracellular 2-HG levels bothin vitro andin vivo . Interestingly, inhibition of 2-HG production had no effect onin vitro IDH1 mutant glioma cell proliferation. In contrast, IDH1 mutant-selective inhibitors provided considerable survival benefitin vivo . However, even with near complete inhibition of intratumoral 2-HG production, not all mutant glioma models responded to treatment. The results suggest that disruption of 2-HG production with brain-penetrant inhibitors in IDH1 mutant gliomas may have substantial patient benefit.